Strategijske smjernice informatizacije Agronomskog fakulteta Sveučilišta u Zagrebu do 2005. godine - Grbavac, Vitomir (Array, 2003)
The process of systematic informatization of the Faculty of Agriculture by 2005 represents an attempt of the Faculty of Agriculture, an institution with rich tradition and good prospects, to meet new and emerging challenges in the area of computer technology. Aim of the paper is to suggest structural changes in the domain of development and application of information and telecommunication technology along with knowledge based on it, which this institution will be introducing in the near future in areas of education, scientific research and management. Having in mind this context, these strategic guidelines will be our response to emerging needs for informatization of the Faculty of Agriculture. This paper offers a strategy, which is aiming at the improvement and standardization of the existing network and information infrastructure of the Faculty of Agriculture.